Pengaturan Persekutuan Perdata Notaris Dalam Perspektif Undang-Undang Jabatan Notaris - Ariwangsa, I Dewa Gede Agung; Yustiawan, Dewa Gede Pradnya (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024), 2024)
The study of this legal issue  civil partnerships in Indonesia and to determine the correlation and relationship between Article to article in UUJNP. The norm condition in this study has a condition of norm disharmony so that the study technique applied is a normative study which has a study focus on legal norms, legal concepts and laws. The study of this legal issue which applies normative research methods has research results regarding the position of notary civil partnerships in Indonesia which have different forms and characteristics from individual partnerships in general. 20 Paragraph 1 UUJNP experiences disharmony with Article 19 Paragraph 1 Letter A UUJNP so this condition must be resolved by reformulating the UUJNP and emphasizing the characteristics of notary civil partnerships which still refer to non-profit purposes because of the possibility that could occur if there are no clear and firm regulations on the form Notary civil associations will experience a shift where notary civil associations will compete to gain profits to finance the operations of their associations.